Detection of Anaplasma phagocytophilum DNA in Deer Keds: Massachusetts, USA - Patrick Pearson; Guang Xu; Eric L. Siegel; Mileena Ryan; Connor Rich; Martin J. R. Feehan; Blake Dinius; Shaun M. McAuliffe; Patrick Roden-Reynolds; Stephen M. Rich (Insects)
Deer keds (Lipoptena spp. and Neolipoptena ferrisi) are hematophagous ectoparasites that primarily infest white-tailed deer (Odocoileus virginianus) and other cervids in the United States. The distribution of deer keds in the northeastern United States and the pathogens they harbor remains relatively unexplored. In this study, we examined the geographical distribution and pathogen prevalence of deer keds in Massachusetts by collecting samples from white-tailed deer and testing for tick-borne pathogens. Deer keds were collected across the state, including in four previously unrecorded counties, indicating a wide distribution. Pathogen screening revealed the presence of Anaplasma phagocytophilum DNA in 30% of the keds, but no other pathogens were detected. The medical and biological significance of detecting A. phagocytophilum DNA in deer keds requires future studies. This research provides a baseline for the distribution and pathogen prevalence of deer keds in Massachusetts and highlights the potential of deer keds as sentinels for monitoring deer-associated microbes.